Adapting Agriculture to Climate Today, for Tomorrow (ACToday) - Ethiopia - Pattni, Ravina; Ward, Kelly (2018)
This brief summarizes findings of a mission of MSc fellows in support of the project entitled ‘Adapting Agriculture to Climate Today, for Tomorrow (ACToday) in Ethiopia’ led by the International Research Institute for Climate and Society (IRI) of Columbia University and implemented in collaboration with CCAFS East Africa. As part of the needs assessment phase over a period of 3 months, the fellows interviewed multiple stakeholders in the agriculture and climate services sectors. These stakeholders included decision-makers from both the public and private sectors in Ethiopia, as well as Ethiopia’s international development partners. This phase of the project focused on gathering information to assess the needs, strengths, and challenges of climate services – specifically data generation, translation, analysis, and dissemination – on a large scale through stakeholder interventions and program activities, and the wheat and livestock value chain analyses.